2016
DOI: 10.1016/j.bpj.2016.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic Diversity Using Bimodal and Unimodal Expression of Stress Response Proteins

Abstract: Populations of cells need to express proteins to survive the sudden appearance of stressors. However, these mechanisms may be taxing. Populations can introduce diversity, allowing individual cells to stochastically switch between fast-growing and stress-tolerant states. One way to achieve this is to use genetic networks coupled with noise to generate bimodal distributions with two distinct subpopulations, each adapted to a stress condition. Another survival strategy is to rely on random fluctuations in gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, under the more complex scenario in which the coupling strength varies randomly (rand-x case), the exploration-exploitation tradeoff leads to a non-zero optimal search rate and unimodal phenotypic distributions are generically preferred. This picture is in complete agreement with the results obtained in [29], where the theoretical benefit of a bimodal distribution of stress response proteins was found to be highest in two-state environments, while more variable and structured environments allow for the selection of unimodal distributions. In addition, we have found that adding a small amount of diffusion to a purely exploitative strategy always leads to an increase of fitness in randx environments, while it is always detrimental in const-x environments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, under the more complex scenario in which the coupling strength varies randomly (rand-x case), the exploration-exploitation tradeoff leads to a non-zero optimal search rate and unimodal phenotypic distributions are generically preferred. This picture is in complete agreement with the results obtained in [29], where the theoretical benefit of a bimodal distribution of stress response proteins was found to be highest in two-state environments, while more variable and structured environments allow for the selection of unimodal distributions. In addition, we have found that adding a small amount of diffusion to a purely exploitative strategy always leads to an increase of fitness in randx environments, while it is always detrimental in const-x environments.…”
Section: Discussionsupporting
confidence: 91%
“…Such models capture the physical and mathematical complexity of these systems starting from minimal assumptions about the environment and/or the space of feasible phenotypes. In more structured cases, the spectrum of viable behaviors appears to be even richer [29].…”
Section: Introductionmentioning
confidence: 99%
“…This result might have been due to the application of the amino acids which were used by microbes as a food source. The slaughterhouse wastes’ hydrolysates contained abundant free amino acids which provided rich nutrients for NJAU4742, while the adversity from the low pH stress also resulted in an obvious promotion of sporulation [ 31 ]. Jian et al [ 32 ] noted that the evolutions of fungal colonies, spore formation and metabolic activity were significantly affected by nutrition, oxygen, pH and temperature during SSF.…”
Section: Discussionmentioning
confidence: 99%
“…Since mating is not taken into consideration, we will not look for speciation according to Mayr's biology speciation concept, where different species are separated if mating does not produce fertile offsprings [5]. Instead, we speak of speciation in terms of differences in phenotype distributions [44], where well-separated peaks can be interpreted as different species while the width of each peak accounts for the intraspecies differentiation.…”
Section: Introductionmentioning
confidence: 99%